Congenital Dislocation of the Fifth Metatarsophalangeal Joint in Adults: Operative Technique. Issue 3 (2nd August 2018) - Jaffe, David E.; Brodsky, James W.
Congenital dislocation of the fifth metatarsophalangeal (MTP) joint can cause significant limitations in a patient's ability to wear a closed shoe. Historic treatment has involved amputation of the digit or attempts at reconstruction. These techniques have had limited success with unreliable correction and/or unacceptable cosmesis. The authors present a detailed, methodical approach to reconstruction of this deformity with a stepwise algorithm that addresses both the bony and soft tissue components of the deformity. With this modern technique, reliable and satisfactory results can be expected.